Public relations - Bernays, Edward L. (Norman : University of Oklahoma Press, 1952)
Edward Bernays explains the underlying philosophy of public relations and the PR methods and practices to be applied in specific cases. He presents broad approaches and solutions as they were successfully carried out in his long professional career.
Chapter 1. Public Relations Today -- Chapter 2. Why Public Relations Knowledge is Vital Today -- Chapter 3. Origins of Public Relations -- Chapter 4. From the Dark Ages to the Modern World -- Chapter 5. American Public Relations from 1600 to 1800 -- Chapter 6. The Public Relations of Expansion, 1800-65 -- Chapter 7. "The Public Be Damned, " 1865-1900 -- Chapter 8. "The Public Be Informed, 1900-19 -- Chapter 9. The Rise of a New Profession, 1919-29 -- Chapter 10. Public Relations Comes of Age, 1929-41-- Chapter 11. The Era of Integration, 1941-51 -- Chapter 12. The Ideal Public Relations Man -- Chapter 13. Extent of Today's Public Relations -- Chapter 14. The Engineering of Consent -- Chapter 15. Typical Action Blueprint for Public Relations Actions -- Chapter 16. Achieving Goals Though the Education of the Public -- Chapter 17. A Typical Survey Finding-America Looks at Nursing -- Chapter 18. Public Relations for a Profession-A Better Deal for Nurses -- Chapter 19. The Truth about House Magazines-Fifty Million Readers Can't Be Wrong -- Chapter 20. Salesmanship and the Public Relations Approach-Hidden Markets in the Human Personality -- Chapter 21. Public Relations in the Theatrical World-The Crisis in the American Theater and Some Possible Solutions -- Chapter 22. Direct Mail: A Challenge to Research in Humanics -- Chapter 23. Advertising In Behind the Time-Culturally -- Chapter 24. A DIfferent Kind of Poll-Preview of American Public Opinion -- Chapter 25. Attitude Polls-Servants or Masters? -- Chapter 26. Public Relations for Public Education -- Chapter 27. Public Relations for Higher Education -- Chapter 28. The Importance of Public Opinion in Economic Mobilization -- Chapter 29. Public Relations and Anglo-American Co-operation-How Can the Americans and the British Understand Each Other? -- Chapter 30. Public Relations as Aid to Ethnic Harmony: Hawaii-The Almost Perfect State -- Chapter 31. Human Relations-The Way to Labor-Management Adjustments -- Chapter 32. An Education Program for Unions -- Chapter 33. How American Business Can Sell the American Way of Life to the American People .
Includes bibliographical references and index.
Keywords: PSYCHOLOGY